The Economic Potential of Industrial Hemp (Cannabis Sativa L.) in the Uttarakhand Himalaya: An Ethno –Historical Study - Vijay Bahuguna; Neha Kukreti (American Journal of Biology and Natural Sciences, 2026)
Industrial hemp (Cannabis sativa L.) has emerged as a sustainable and eco –friendly crop with vast industrial potential. Uttarakhand became the first Indian state to legalize the commercial cultivation of Industrial hemp in 2015.recognizing its environmental and economic benefits. Grown primarily in the hilly terrains of the Lesser Himalayas, hemp requires minimal water, improves soil quality and prevents erosion-making it ideal for mountain agriculture. The state policy restricts cultivation for low-THC (below 0.3%) varieties, ensuring non-narcotic use and compliance with national regulations. The crop provides multipurpose raw materials; fibers for textiles, and hurd for construction materials such as hemp crate. However challenges such as limited processing infrastructure, seed standardization and regulatory awareness among farmers hinder large scale adaptation with appropriate policy support, research and industrial investment, industrial hemp could significantly contribute to Uttarakhand’s rural economy, sustainable agriculture and green industry development. The study of industrial hemp in Uttarakhand, when viewed through the Annals and Ethno-historical frameworks, transcends economic analysis. It becomes a narrative of environmental adaptation, cultural resilience and the re-emergence of traditional ecological knowledge within modern sustainability paradigms. An Annals –inspired study can use environmental history, economic data, and agrarian records to trace long-term change. An Ethno-historical study can use field interviews, folk tradition, and material artifacts to capture local memory and cultural continuity.